2014
DOI: 10.1155/2014/301751
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of a Standard Genetic Algorithm with a Hybrid Genetic Algorithm Applied to Cell Formation Problem

Abstract: Though there are a number of benefits associated with cellular manufacturing systems, its implementation (identification of part families and corresponding machine groups) for real life problems is still a challenging task. To handle the complexity of optimizing multiple objectives and larger size of the problem, most of the researchers in the past two decades or so have focused on developing genetic algorithm (GA) based techniques. Recently this trend has shifted from standard GA to hybrid GA (HGA) based appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Computational results showed that the proposed algorithm able to reach the optimal or near to global optimal rapidly. Javaid et al [13] combined traditional Genetic (GA) with a Local Search Heuristic (LSH) to fix problems related to cell formation. A wide range of problems has been solved by hybrid genetic algorithm (HGA) and GA.…”
Section: Introductionmentioning
confidence: 99%
“…Computational results showed that the proposed algorithm able to reach the optimal or near to global optimal rapidly. Javaid et al [13] combined traditional Genetic (GA) with a Local Search Heuristic (LSH) to fix problems related to cell formation. A wide range of problems has been solved by hybrid genetic algorithm (HGA) and GA.…”
Section: Introductionmentioning
confidence: 99%